The Influence of a Scientific Approach with Fun Science on Learning Motivation and Understanding of Physics Concepts - Gultom, Roidah Aryani; Imran, Ali; Sibagariang, Muhammad Taufik (Institut Agama Islam Negeri Padangsidimpuan, 2024)
The objective of this study is to know about the influence of learning Science using scientific approach with fun science to learning motivation of JUNIOR HIGH SCHOOL students, the influence of learning Natural Science using scientific approach with fun science towards an understanding of the concept of Natural Science of JUNIOR HIGH SCHOOL students, and the influence of learning Natural Science using scientific approach with fun science to learning motivation and understanding of the concept of Natural Science of JUNIOR HIGH SCHOOL students. The object of this research is the VII grade students with